Sparc (Osteonectin): new insight into the function and regulation = Sparc (Osteonectin): nuevos conocimientos sobre sus funciones y regulación - Torres Núñez, Eva (Universitat de Barcelona, 2014)
Tesi realitzada a l'Instituto de Investigaciones Marinas, IIM-CSIC, de Vigo The Extracellular Matrix (ECM) is a complex network secreted by cells that serves as a structural element in tissues and also influences their development and physiology. More specifically, the extracellular matrix helps cells to bind together and regulates several cellular functions such as adhesion, migration, proliferation and differentiation. It is composed of growth factors, proteoglycans, structural proteins and matricellular proteins. Osteonectin, also named Sparc (Secreted Protein Acidic and Rich in Cysteine) or BM-40 (Membrane Protein-40), is a multifunctional glycoprotein that belongs to the matricellular protein family. This group modulates matrix-cellular interactions and takes part in several cell functions, rather than playing a role in the cell structure. Sparc is known to have high affinity with calcium ions and was first discovered as the major component of ECM in mineral tissues, although it has since been located in many other tissues. Sparc expression is high during early development but remains low in adult life. However, it is expressed in tissues under renewal, tissue repair or tumorigenesis. Since Sparc is able to interact with multiple molecules, many important functions have been attributed to this protein, including counteradhesion, the regulation of cell proliferation and angiogenic activity. Analysis of the results obtained during this PhD Thesis leads to the following conclusions: • Sparc is as an important regulator of embryonic haematopoiesis during early development in zebrafish. Specifically, it mediates erythroid progenitor cell development regulating gata1 and βe3globin expression. • Similar defects in blood phenotypes of sparc and fgfs knockdowns and the capacity to partially rescue the fgf21 blood phenotype places sparc downstream of fgf21 signaling genetic network. • UV exposure induces an increase in the p53 and sparc expression • According with the conclusion 3, a possible molecular mechanism ...